(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The objective of the research is to review the political pressures exerted by countries on Syria since 2011 until 2017. To study the economic dimensions that resulted from these pressures and their impact on the growth of GDP and the growth of the GDP of the productive sectors in Syria, , And to follow the articles and scientific references on the political pressures that the Syrian Arab Republic was exposed during the war period on the Syrian, and then study the impact of political pressure on economic growth during the war on Syria, and was using the program Spss v24, and the researcher has found the following main findings: The Arab Republic has been subjected to many political pressures at the regional, Arab and international levels. These political pressures, using sanctions, banning and freezing foreign dealings, and activating armed groups to destroy the Syrian economy, were designed to gain political gains. Political pressures have succeeded in negatively affecting the growth of the Syrian economy, but have failed to achieve their political gains. The Syrian economy has suffered significant material losses in all productive sectors during the war against Syria. There is a statistically significant impact of political pressures on the GDP growth of agriculture, forestry and livestock, industry, mining and quarrying, wholesale and retail trade and reform, government services, and non-profit organizations. There is no statistically significant impact of political pressures on the GDP growth of construction, transport, storage, communications, finance, insurance, real estate, community services and personal services. The industrial sector is the most affected by the political pressures followed by the agricultural sector, and then the wholesale and retail trade and reform.